2008
DOI: 10.1002/ajmg.a.32354
|View full text |Cite
|
Sign up to set email alerts
|

Shwachman–Diamond syndrome is associated with structural brain alterations on MRI

Abstract: Shwachman-Diamond syndrome (SDS) is an autosomal recessive condition that results from mutations in the SBDS gene, at chromosome 7q11. Main features include exocrine pancreatic failure, neutropenia and skeletal dysplasia. This study investigated brain structures by magnetic resonance imaging (MRI) in patients with SDS. MRI of the brain was performed in nine patients (7 males, age range 7-37 years) with SDS and mutations in the SBDS gene and in 18 age- and gender-matched controls. MRI images were assessed visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
0
27
1
1
Order By: Relevance
“…Ataxia is not a manifestation of Shwachman-Diamond syndrome; however neurological abnormalities and mild MRI changes consistent of hypoplasia of the cerebellar vermis, mesencephalon, pons, and medulla and corpus callosum have been reported (Toiviainen-Salo et al 2008). The patients was also tested for RECQL4 mutations as pancytopenia and developmental delay have been reported in this spectrum of disorders, which are also characterized by early aging, skin abnormalities and sometimes dystrophic nails (Knoell et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Ataxia is not a manifestation of Shwachman-Diamond syndrome; however neurological abnormalities and mild MRI changes consistent of hypoplasia of the cerebellar vermis, mesencephalon, pons, and medulla and corpus callosum have been reported (Toiviainen-Salo et al 2008). The patients was also tested for RECQL4 mutations as pancytopenia and developmental delay have been reported in this spectrum of disorders, which are also characterized by early aging, skin abnormalities and sometimes dystrophic nails (Knoell et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal forms have been described, with respiratory distress, narrow thorax, pancytopenia [61,62], and especially neurological involvement (mental retardation) [63], predominant gastrointestinal disorders (gluten intolerance), growth retardation in the second year of life, and predominant bone involvement suggestive of a constitutional bone disorder [64]. Depending on the presenting manifestations, differential diagnoses include Cystic fibrosis, Pearson's syndrome (characterized by cytologic abnormalities and especially mitochondrial respiratory chain defects), Fanconi anemia (distinguished by the constitutional karyotype) and gluten intolerance.…”
Section: Congenital Neutropenia - Classification and Etiologymentioning
confidence: 99%
“…36,37 In a recent study, Kerr and colleagues 10 reported on the neuropsychological function in 34 children with SDS, comparing them to 13 sibling controls as well as 20 patients with cystic fibrosis matched for age and gender. Patients with SDS ranged widely in their abilities compared with controls, from severely impaired to superior in some areas measured.…”
Section: Neurocognitive Manifestationsmentioning
confidence: 99%